Fostering organizational citizenship behavior (OCB) through human resources empowerment (HRE) - Nezakati, Hossein *; Kohzadi, Vajihe; Karimi, Faraz; Asgari, Omid (2009)
This research attempts to build a model to present an approach for achieving organizational citizenship behavior (OCB) through human resource empowerment (HRE). Process procedures used in building this model were: 1) preparation of individuals and management; 2) requirements for empowerment process and utilization of five principles from Deming Principles; 3) three dimensions of HRE process and their symbolic aspects; 4) OCB dimensions in their innate forms and their enforcement during these procedures; 5) instrumental factors in creating OCB and outcome of HRE in one procedure; 6) OCB symbolism; and 7) consequences of OCB. The results of this study showed that eight factors out of eleven (73 percents of factors) that make up OCB and consequences of HRE are analogous indicating the fundamental relationship of HRE with OCB.